2007
DOI: 10.1038/nature05884
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity of Lepidoptera in tropical and temperate forests

Abstract: For numerous taxa, species richness is much higher in tropical than in temperate zone habitats 1 . A major challenge in community ecology and evolutionary biogeography is to reveal the mechanisms underlying these differences. For herbivorous insects, one such mechanism leading to an increased number of species in a given locale could be increased ecological specialization, resulting in a greater proportion of insect species occupying narrow niches within a community. We tested this hypothesis by comparing host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
438
8
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(481 citation statements)
references
References 31 publications
26
438
8
9
Order By: Relevance
“…Although we found that generalist and not specialist herbivores contributed to higher herbivore species richness at lower latitudes, we cannot draw any clear conclusions about possible patterns of herbivore specialization across the latitudinal gradient (3,5). Our study was not designed to exhaustively measure herbivore diet breadth.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although we found that generalist and not specialist herbivores contributed to higher herbivore species richness at lower latitudes, we cannot draw any clear conclusions about possible patterns of herbivore specialization across the latitudinal gradient (3,5). Our study was not designed to exhaustively measure herbivore diet breadth.…”
Section: Resultsmentioning
confidence: 94%
“…As a result, species at lower latitudes are likely to have higher levels of specialization to lessen competition and greater defenses to reduce predation (2). For plant-herbivore interactions in particular, it is expected that at lower (tropical) latitudes, abundance and species richness of insect herbivores will be higher, and, therefore, lower latitudes will also have more specialized herbivores and plants will suffer greater biomass loss to herbivory (3)(4)(5). Consequently, this herbivore species latitudinal gradient is likely to impose stronger herbivore pressure on plants at lower latitudes (6)(7)(8).…”
mentioning
confidence: 99%
“…(a) Biological simplification The huge reduction in tree species diversity (table 2) will inevitably lead to a comparable reduction in the diversity of animals that use trees, especially the legions of herbivorous insects: plant biodiversity begets animal biodiversity [59][60][61]. Not only is diversity reduced at the taxonomic level, but clearly oil palm plantations are architecturally much simpler than forests, with fewer canopy layers, and less diverse elements of, for example, lianas, epiphytes and litter (table 2).…”
Section: Causes Of Biodiversity Lossmentioning
confidence: 99%
“…In particular, phytophagous insect species previously considered to be polyphagous are frequently found to be mixtures of genetically differentiated, specialist taxa, each feeding on a restricted range of host plants (Berlocher and Feder, 2002;Drès and Mallet, 2002;Dyer et al, 2007;Feder and Nosil, 2010;Matsubayashi et al, 2010). These specialized taxa display a recurrent pattern of host-plant associations, together with partial or complete reproductive isolation in sympatry.…”
Section: Introductionmentioning
confidence: 99%